(untitled) (Environment & Health, 2017)
Objectives: We studied the peculiarities of the forming of thyroid cancer incidence among the population in different regions of Ukraine, determined a character and an intensity of its increase in recent decades. Materials and methods: We analyzed a dynamics of thyroid cancer incidence according to the findings of the National Cancer Register and the regional endocrine dispensaries for the period of 1991-2013 in different regions. We applied the method of regression analysis. A significance of the differences was assessed with the help of Student’s coefficient. Results: Obtained results demonstrate a swift growth of thyroid cancer incidence in all regions of Ukraine, it is the most expressed in the highly industrialized regions and in the zones of the intensive agricultural activity as well. These data indicate a possible role of the other anthropogenic factors, besides radiation and iodine deficiency. In this case chemical pollutants (so-called endocrine destroyers) are of great importance because they can damage the function of thyroid gland. It requires the further single-minded research.